Developing social skills as a way of preventing and reducing risk behaviors in adolescents En el desarrollo de habilidades sociales como vía de prevención y reducción de conductas de riesgo se prestó atención a la toma de decisiones, el control de las emociones, la autoestima y la asertividad como contenido esencial de la intervención educativa canalizada a través de talleres tutoriales. Adicionalmente, se eliminó la primera tabla y se mejoró el aparato crítico, a partir de completar los asientos de las referencias y su correspondencia con las citacionesEs necesario que expresen su conformidad con estos cambios. Dr. C. Manuel N. Montejo LorenzoEditor Jefe - Cacho Becerra, Zaida Violeta; Silva Balarezo, Mariana Geraldine; Yengle Ruíz, Carlos (Transformación, 2024)
Objective: The article aims at preventing and reducing risk behaviors by suggesting to carry out tutorial workshops on social skills.Methods: The design used was quasi-experimental including survey and a questionnaire as instrumental techniques. The questionnaire was validated at the level of content, criteria, and construction. The population was formed by students of first to the fifth year of secondary; the sample was selected with a non-probabilistic intentional sampling. The information collected in both the previous and subsequent tests was subjected to descriptive statistical analysis and inferential statistical analysis to test the hypothesis, using the T-test.Results: A system of workshops on social skills is devised as a way of facing risk behavior. Decision making, control of emotions, self-esteem, and assertiveness are the subjects of attention in these workshops. These workshops pursue the participation of students in the transformation of their thinking and attitudes towards risk behaviors.Conclusions: The tutorial workshops of social skills contribute to the correct orientation of the adolescents and to the strengthening of their thoughts and positive behaviors, produces positive changes in the risk behaviors of the adolescents and favors their prevention.
Keywords: Basic skills; behaviors; violence; aggressiveness; bullying